Kajian Filsafat Hukum Alam Irrasional Thomas Aquinas dan Rasional Hugo Grotius dan Imannuel Kant dalam Konteks Indonesia yang Religius - Melia Lau; Suyato Oei; Sugiarto, Sugiarto; Parningotan Malau (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study delves into the philosophical foundations of natural law, contrasting the irrational theories of Thomas Aquinas with the rational perspectives of Hugo Grotius and Immanuel Kant, examining their relevance within Indonesia’s deeply religious and pluralistic context. Aquinas argues that natural law is divinely ordained and serves as a universal moral guide, where law and morality are intrinsically linked. On the other hand, Grotius proposes that while natural law originates from divine will, human reason enables individuals to comprehend it, even without divine revelation. Kant’s philosophy shifts the focus to moral autonomy and the freedom of individuals, emphasizing that legitimate law must be based on principles of universal morality that respect human dignity. In the context of Indonesia, with its diverse religious landscape, integrating these philosophical ideas provides a balanced approach to the interaction between secular law, religious teachings, and moral values. The research adopts a juridical-normative methodology with a conceptual and legislative approach, analyzing secondary legal sources to explore how natural law influences Indonesia's legal system. The findings indicate that while Indonesia's legal system primarily follows positive law, it would benefit from incorporating the moral and spiritual aspects derived from natural law theory. The study concludes that Indonesia’s legal system can achieve a more substantive form of justice by integrating the principles of Aquinas, Grotius, and Kant, thus ensuring a more harmonious blend of legal certainty, moral integrity, and religious principles in the country’s laws.